1996
DOI: 10.1111/j.1600-051x.1996.tb00558.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between clinical attachment loss and the duration of insulin‐dependent diabetes mellitus (IDDM) in children and adolescents

Abstract: The periodontal status of 77 diabetic children and adolescents, and 77 paired, systemically-healthy, sex- and age-matched control subjects, was clinical examined. Fasting blood glucose, fructosamine and glycosylated haemoglobin (HbA1) values were determined. The mean periodontal pocket depths, clinical attachment levels and the parameters to assess diabetes mellitus from the diabetic group were significantly higher than those of the controls. We found a positive correlation between the duration of diabetes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 47 publications
3
40
0
3
Order By: Relevance
“…The results were consistent with the studies of Beneveniste et al, 17 Ervasti et al, 13 De-Pommereaun et al, 18 Firatli et al, 19 Aren et al 20 and Campus et al 21 who found similar observations. Likewise, on comparison of PPD between the diabetic and nondiabetic groups, a mean depth score obtained for diabetic group was 4.43 AE 0.97 mm and 3.96 AE 0.75 mm for non-diabetic group which was also statistically significant (p < 0.005).…”
Section: Discussionsupporting
confidence: 91%
“…The results were consistent with the studies of Beneveniste et al, 17 Ervasti et al, 13 De-Pommereaun et al, 18 Firatli et al, 19 Aren et al 20 and Campus et al 21 who found similar observations. Likewise, on comparison of PPD between the diabetic and nondiabetic groups, a mean depth score obtained for diabetic group was 4.43 AE 0.97 mm and 3.96 AE 0.75 mm for non-diabetic group which was also statistically significant (p < 0.005).…”
Section: Discussionsupporting
confidence: 91%
“…lin direncine bağlı olarak gelişebilen endokrin bir hastalıktır (7,8). Diyabetli hastalarda tükürük salgısının koyulaşması ve miktarının azalması nedeni ile tükürüğün dişleri yıkayıcı ve çiğnemeyi kolaylaştırıcı etkisi kaybolabilmektedir (9).…”
Section: Discussionunclassified
“…In einigen Studien wurde eine Korrelation zwischen Diabetesdauer und parodontaler Destruktion gefunden [17,18,26], wohingegen in anderen Untersuchungen kein Zusammenhang zwischen der Dauer des Diabetes und dem Parodontalzustand nachweisbar war [33].…”
Section: Discussionunclassified
“…Some studies reported a correlation between the duration of diabetes and periodontal destruction [17,18,26] while others detected no connection between the disease's duration and periodontal status [33].…”
Section: Secondary Diseases and Complicationsmentioning
confidence: 99%